Almost Sg- Continuity in Topological Spaces - Darwesh, Halgwrd M.; Hessean2, Nawroz O. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In the present paper, we introduce a new class of functions in between topological spaces, namely the class of almost -continuous functions. Characterizations and basic properties of this class of functions are obtained as well as the relationships of it with some other classes of functions are studied.
Keywords: Sgopen set; semiopen set; gclosed set; Sgcontinuous function almostSgcontinuous Function